2013
DOI: 10.3325/cmj.2013.54.444
|View full text |Cite
|
Sign up to set email alerts
|

Availability of mental health service providers and suicide rates in Slovenia: a nationwide ecological study

Abstract: AimTo investigate the influence of socioeconomic factors, mental health service availability, and prevalence of mental disorders on regional differences in the suicide rate in Slovenia.MethodsThe effects of different socioeconomic factors, mental health service availability, and mental disorders factors on suicide rates from 2000-2009 were analyzed using a general linear mixed model (GLMM). Pearson correlations were used to explore the direction and magnitude of associations.ResultsAmong socioeconomic factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 51 publications
4
28
0
3
Order By: Relevance
“…Recently, this observation was corroborated by the main finding of a nationwide ecology study about the availability of mental health service providers and suicide rates in Slovenia (Korošec Jagodič et al, 2013). The study showed that regional differences might be influenced by unequal availability of mental health services and the efficiency of depressive disorder treatment.…”
Section: Graph 1 Standardised Suicide Rates In Slovenia Between 1985 mentioning
confidence: 66%
“…Recently, this observation was corroborated by the main finding of a nationwide ecology study about the availability of mental health service providers and suicide rates in Slovenia (Korošec Jagodič et al, 2013). The study showed that regional differences might be influenced by unequal availability of mental health services and the efficiency of depressive disorder treatment.…”
Section: Graph 1 Standardised Suicide Rates In Slovenia Between 1985 mentioning
confidence: 66%
“…Moreover, the importance of crisis intervention for help-seeking individuals has been demonstrated in two East-European countries, where a reverse correlation between suicide rates and the number of physicians was present [ 208 , 209 ]. This changed with an increasing number of health care professionals and an increasing treatment rate of depression.…”
Section: Preventionmentioning
confidence: 99%
“…Čeprav naredi samomor skoraj ena četrtina manj Slovencev kot na primer še pred dvema desetletjema, od leta 2010 v Sloveniji po podatkih Inštituta za varovanje zdravja (2011) ponovno beležimo porast števila samomorov. Domači in tuji strokovnjaki ta porast pripisujejo neugodnim družbenim razmeram in padcu življenjskega standarda zaradi gospodarske krize, ki je zajela svet v zadnjih nekaj letih (Groleger, 2009;Stuckler, et al, 2009;Karanikolos, et al, 2013;McDaid, et al, 2013;Korošec Jagodic, et al, 2013;Pompili, et al, 2014). Po podatkih v Sloveniji tako v zadnjem času zaradi samomora letno umre približno 436 prebivalcev, od tega 347 moških in 89 žensk, njihova starost pa je v povprečju 57 let (Kalin, 2012).…”
Section: Uvodunclassified
“…While almost 25 % fewer Slovenes committed suicide than even two decades ago, Slovenia has recorded an increase in the number of suicides since 2010 according to data compiled by the Institute of Public Health (2011). Domestic and foreign experts have attributed this increase to the unfavourable social situation and the decline in the standard of living due to the economic crisis that has engulfed the world in recent years (Groleger, 2009;Stuckler, et al, 2009;Pompili, et al, 2014;Karanikolos, et al, 2013;McDaid, et al, 2013;Korošec Jagodic, et al, 2013). According to the statistics, 436 inhabitants of Slovenia die of suicide every year, of whom 347 are male and 89 are female, with the average age being 57 years (Kalin, 2012).…”
Section: Introductionmentioning
confidence: 99%